Metagenomic insights into the effects of cosmetics containing complex polysaccharides on the composition of skin microbiota in females - Cui, Shumao; Pan, Mingluo; Tang, Xin; Liu, Guangrong; Mao, Bingyong; Zhao, Jianxin; Yang, Kaiye (Frontiers in Cellular and Infection Microbiology, 2023)
The use of cosmetics has become a habit for women. However, their influence on the microbial diversity of the skin has rarely been studied. Herein, the effect of cosmetics containing complex polysaccharides on the skin bacterial microbiota of female forehead and cheek areas was analyzed. Eighty volunteers were recruited and split into two groups (40 people each); one group was treated with cosmetics containing complex polysaccharides and the other with basic cream for 28 days. Skin samples were collected using sterilized cotton swabs, and 16S rDNA high-throughput sequencing was used to analyze the changes in skin bacterial microbiota composition before and after the intervention. A total of twenty-four phyla were detected in the forehead and cheek skin samples of 80 volunteers, the top three of which were Proteobacteria, Firmicutes, and Actinobacteria. The main genera of the forehead skin bacterial microbiota were Cutibacterium (11.1%), Acinetobacter (10.4%), Enterococcus (8.9%), Ralstonia (8.8%), and Staphylococcus (8.7%), while those of the cheek skin bacterial microbiota were Staphylococcus (20.0%), Ralstonia (8.7%), Propionibacterium (7.9%), Acinetobacter (7.2%), and Bifidobacterium (6.0%). Compared with basic cream, the use of cosmetics containing complex polysaccharides significantly increased the relative abundance of Staphylococcus and Bacillus in the forehead and cheek and reduced the relative abundance of Propionibacterium and Bifidobacterium. Thus, cosmetics containing complex polysaccharides could modify the composition of skin bacterial microbiota, which may help to maintain stable conditions of the skin.